PENGEMBANGAN MEDIA PERMAINAN SPIN (RODA PUTAR) PADA MATERI BANGUN DATAR SISWA KELAS IV SEKOLAH DASAR NEGERI 6 RAMBANG - Yolanda Tri Septiani; Destiniar; Putri Dewi Nurhasana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to produce a learning product in the form of a spin game media (swivel wheel) on flat shape material forgrade IV elementary school students that is valid, practical, andeffective. The type of research conducted is Research & Development (R&D) with the development model used, namely the ADDIE model. The results showed that: 1) The quality of the swivel wheel media seen from the aspect of validity was included in the "very valid" category based on the results of the validation of experts getting a percentage value of 82.3%, 2) The quality of the media seen from the practical aspect was categorized as "very practical" from the trial one to one gets a percentage of 90% with the criteria of "very practical" and the results of the small group trial get a percentage of 91.75% with the criteria of "very practical", and 3) The effectiveness of the resulting media is categorized as "effective" from the trials learning out comes get a percentage value of 80%. So it can be concluded that the rotating wheel media meets the criteria of validity, practicality, and effectiveness so that it can be used in the learning process.